2006
DOI: 10.1186/1476-069x-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Plasma organochlorine concentrations and bone ultrasound measurements: a cross-sectional study in peri-and postmenopausal Inuit women from Greenland

Abstract: Background: Inuit women are highly exposed through their traditional seafood based diet to organochlorine compounds, some of them displaying endocrine disrupting properties. We hypothesized that this exposure might be related to bone characteristics that are altered in osteoporosis, because hormone deficiency is a known risk factor for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 37 publications
1
45
2
5
Order By: Relevance
“…Exposure to PCB in human populations near the Baltic coast resulted in gender-specific changes in bone quality, as assessed by altered bone mineral density, with a greater effect in males (Hodgson et al 2008). Increased vertebral fractures and incidences of osteoporosis were found in fishermen and fishermen's wives exposed to persistent organic pollutants (POP) through dietary intake of fatty fish from the Baltic (Alveblom et al 2003), while three independent studies found no statistically-significant association between bone mineral density and organochlorine concentrations after adjustment for age and body mass index (Wallin et al 2005;Côté et al 2006;Rignell-Hydbom et al 2009). Furthermore, alterations in bone quality were demonstrated for wildlife from organohalogencontaminated environments (Fox et al 2008;Johnson et al 2009;Lind et al 2003;Murtomaa et al 2007;RodriguezNavarro et al 2006;Roos et al 2010;Sonne et al 2004).…”
Section: Perinatal Exposure To Environmental Contaminants Detected Inmentioning
confidence: 97%
“…Exposure to PCB in human populations near the Baltic coast resulted in gender-specific changes in bone quality, as assessed by altered bone mineral density, with a greater effect in males (Hodgson et al 2008). Increased vertebral fractures and incidences of osteoporosis were found in fishermen and fishermen's wives exposed to persistent organic pollutants (POP) through dietary intake of fatty fish from the Baltic (Alveblom et al 2003), while three independent studies found no statistically-significant association between bone mineral density and organochlorine concentrations after adjustment for age and body mass index (Wallin et al 2005;Côté et al 2006;Rignell-Hydbom et al 2009). Furthermore, alterations in bone quality were demonstrated for wildlife from organohalogencontaminated environments (Fox et al 2008;Johnson et al 2009;Lind et al 2003;Murtomaa et al 2007;RodriguezNavarro et al 2006;Roos et al 2010;Sonne et al 2004).…”
Section: Perinatal Exposure To Environmental Contaminants Detected Inmentioning
confidence: 97%
“…In this particular cohort study, univariate analyses showed significant negative associations between serum 2,2′,4,4′,5,5′-hexachlorbiphenyl (PCB 153), which is the most abundant PCB congener in the human body, and BMD evaluated using dual energy x-ray absorptiometry [40]. In addition, Côté et al [2] reported that the plasma concentrations of PCB 153 in Inuit women were inversely correlated with their bone density as evaluated by quantitative ultrasound in univariate analyses; however, this correlation did not reach statistical significance in multivariate analyses. In addition, high concentrations of PCB 153 were reported to act as an antagonist of the human SXR [34].…”
Section: Discussionmentioning
confidence: 96%
“…La collecte des données a été décrite précédemment par Côté et al (2006). Les critères requis pour participer à l'étude étaient d'être une femme âgée entre 49 et 64 ans, née au Groenland.…”
Section: Projet Groenland 2000 -2002unclassified
“…Au total, 167 femmes ont été invitées à participer à l'étude et à se présenter à la clinique de soins de santé de première ligne de l'Hôpital Queen Ingrid. Huit d'entre elles ont refusé, six autres ont été exclues pour cause de maladies (VIH, maladies mentales, grippe); finalement, 153 Inuites ont participé à l'étude (Côté et al 2006). Les participantes ont répondu à un questionnaire adapté de celui de l'étude MEDOSMediterranean osteoporosis study questionnaire (Dequeker et al 1991), lequel a été administré en danois par un interviewer lors d'une rencontre face-à -face.…”
Section: Projet Groenland 2000 -2002unclassified
See 1 more Smart Citation